PENGARUH KARAKTERISTIK PERUSAHAAN DAN AUDITOR SWITCHING TERHADAP AUDIT DELAY DENGAN SPESIALISASI INDUSTRI AUDITOR - Stephanie Adelia Tunggal; Herlina Lusmeida (Universitas Kristen Krida Wacana, 2019)
The aims of this research are to analyze the factors that influence audit delay in companies listed in Indonesia Stock Exchange (IDX) in 2014-2017 periods. Samples obtained by using purposive sampling are 84 companies. The independent variables are company size, profitability, leverage, and auditor switching. The moderating variable is auditor specialization with audit delay as the independent variable. This research uses Multiple Regression Model and Moderated Regression Analysis (MRA) with SPSS 25. The results of this research are size have negatively significant influence on audit delay, profitability have negatively significant influence on audit delay, leverage have positively significant influence on audit delay, auditor switching have positive but not significance influence on audit delay, auditor specialization have positive but not significant influence on audit delay, specialization auditor weaken the negative relationship of company size with audit delay, specialization auditor strengthens the negative relationship of profitability with audit delay, specialization auditor strengthens the positive relationship of leverage with audit delay, specialization auditor strengthens the positive relationship of auditor switching with audit delay,Keywords: audit delay, company size, profitability, auditor switching, and auditor specialization